The Ottoman Era in Hama: al‑Ṭayārah al‑Ḥamrā’ Palace, a ‘Reception’ House of the 18th Century - Fayyad, Imane (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
The al‑Ṭayārah al‑Ḥamrā’ palace located in the Bāb al‑Nāʻwra (noria) district in the old city of Hama covers an area of approximately 1554 m². This palace, attributed to the al‑Kīlāni family, was used as a reception house for official guests; it was entirely destroyed in 1982, the day the old city was bombed. This study aims at demonstrating what makes it a reception house from the Ottoman era (18th century) and increasing knowledge of this period that has received less attention even though architectural and decorative wealth was valorised. To this end, we will conduct an analysis of its main architectural and decorative elements.